Design, synthesis, and evaluation of benzhydrylpiperazine-based novel dual COX-2/5LOX inhibitors with anti-inflammatory and anticancer activity - Saraf P.; Bhardwaj B.; Verma A.; Siddiqui M.A.; Verma H.; Kumar P.; Srivastava S.; Krishnamurthy S.; Srikrishna S.; Shrivastava S.K. (My University, 2025)
Piperazine derivatives were screened using the ChEMBL database, paving the way for the design, synthesis, and evaluation of a novel series of dual COX-2/5-LOX inhibitors and identifying their role in mitigating cancer cell proliferation. Compound 9d with 4-Cl substitution at the terminal phenyl ring showed promising inhibition of COX-2 (IC50 = 0.25 ± 0.03 μM) and 5-LOX (IC50 = 7.87 ± 0.33 μM), outperforming the standards celecoxib (IC50 = 0.36 ± 0.023 μM) and zileuton (IC50 = 14.29 ± 0.173 μM), respectively. The two most active derivatives 9d and 9g indicated a significant anti-inflammatory response in a paw edema model by inhibiting PGE2, IL-6, and TNF-α and an increase in IL-10 concentrations. Interestingly, 9d effectively reduced pain by 55.78%, closely comparable to the 59.09% exhibited by the standard indomethacin, and was also devoid of GI, liver, kidney, and cardiac toxicity. Furthermore, 9d demonstrated anti-cancer potential against in vitro A549, COLO-205, and MIA-PA-CA-2 human cancer cell lines and an in vivo Drosophila cancer model. The pharmacokinetic investigations revealed that 9d has good oral absorption characteristics. © The Royal Society of Chemistry 2025.